Cancer causing viruses and the role of laboratory medicine: literature review and perspectives - Ana Maria Passos; Celso Francisco Hernandes Granato (Sociedade Brasileira de Patologia Clínica, 2013)
Cancer-causing viruses are responsible for up to 20% of cancers with infectious etiology, representing a serious public health problem worldwide. Since the discovery of the first human cancer-causing virus, several others have been associated with neoplasias. Recent advances in technologies for the determination of genomic and proteomic profiles have resulted in the discovery and availability of tumor markers with potential application in the screening, diagnosis, prognosis and treatment of cancer. Therefore, laboratory medicine has stood out as a fundamental tool in the prevention and management of these diseases.